Integrating Technology Adoption, Use, and Value: A Study of Applications Delivery - Oliveira, Aurea Beatriz Soares de; Oliveira, Deyvison de Lima; Gonçalves, Clayton Pereira (Revista de Negócios, 2023)
The objective of this research is to identify and analyze determining factors in the adoption and use of delivery applications and their relationship with the performance of adopting companies, through an extension of the Unified Theory of Acceptance and Use of Technology (UTAUT2) model. Its contribution lies in the incorporation of process and financial performance variables into the model for a business to business (B2B) purchasing context in which the adoption of technology is optional (voluntary) for organizations. The methodological approach adopted was a survey, developed on an electronic platform and applied to a population of 702 companies using delivery applications in the food service sector. For data analysis, Structural Equation Modeling was used, specifically, Partial Least Squares (PLS), through the SmartPLS software. Among the main results, the following stand out: there is a relationship between the facilitating conditions and the intention to use applications; performance expectation is associated with intended use; the intended use is associated with the usage behavior; the use is associated with the performance of processes that, consequently, influences the financial performance of the firm. The final research model makes it possible to integrate adoption and use with the technology’s business value, phenomena that are usually treated separately in the literature.